2014
DOI: 10.4314/star.v3i2.5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Integrated Nutrient Management on Yield and Yield Components of Food Barley (<i>Hordeum vulgare</i> L.) in Kaffa Zone, Southwestern Ethiopia

Abstract: Article Information Declining soil fertility is one of the major problems causing yield reduction of barley in Southwestern Ethiopia. Therefore, field experiments were, carried out at Adiyo and Ghimbo districts, Kaffa Zone, Southwestern Ethiopia, to determine the effects of combined application of farm yard manure (FYM) and vermi compost (VC) with inorganic NP on growth, yield and yield components of food barley. The treatments included combinations of two rates (2.5 and 5 t ha-1) of FYM and two rates (2.5 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 11 publications
4
9
0
Order By: Relevance
“…The current result is in agreement with Mitiku et al (2014). The smallest numbers of tillers per plant could be attributed to the limited supply of plant nutrition from compost and/or FYM at the initial stages of growth.…”
Section: Yield and Yield Components Of Malting Barleysupporting
confidence: 90%
“…The current result is in agreement with Mitiku et al (2014). The smallest numbers of tillers per plant could be attributed to the limited supply of plant nutrition from compost and/or FYM at the initial stages of growth.…”
Section: Yield and Yield Components Of Malting Barleysupporting
confidence: 90%
“…Effective Tillers: The attainment of higher number of effective tillers might be due to the synergetic combination effects of organic and inorganic fertilizers (Wubshet Demissie et al, 2017). This is consistent with Mitiku Woldesenbet et al (2014) who observed that application of 5 t ha -1 farmyard manure along with 75% of recommended NP gave highest number of productive tillers m -2 and highest number of grains per spike at Adiyo and Ghimbo, respectively. Number of Kernel: The mean number of kernel per plant was significantly affected by application of NPS and FYM and result the applied treatment indicated integrated nutrient management (Tariku Beyene et al, 2018).…”
Section: Yield and Yield Components Of Barleysupporting
confidence: 90%
“…Demissie et al (2017) found significantly higher plant height of barley with the integrated application of organic and inorganic fertilizers in Wolmera district. Correspondingly, Mitiku Woldesenbet et al (2014) found a significant effect of combined application of organic and inorganic fertilizers on plant height barley at Adiyo and Ghimbo with the application of 5 t•ha −1 farmyard manure + 75% of recommended NP and 5 t•ha −1 vermicompost and 75% of recommended NP. Likewise, Getachew Agegnehu (2009) reported that the use of organic manures in combination with mineral fertilizers maximized the plant height of barley.…”
Section: Integrated Effect Of Organic and Inorganic Fertilizers On Fomentioning
confidence: 95%
See 2 more Smart Citations